BEYOND THE NIGHTCAP: A NARRATIVE REVIEW OF ALCOHOL’S IMPACT ON SLEEP ARCHITECTURE, CIRCADIAN RHYTHMS, AND RECOVERY - Martyna Susek,; Amadeusz Furmanek, (International Journal of Innovative Technologies in Social Science, 2026)
Background: Alcohol is one of the most commonly used substances to facilitate sleep, yet its impact on sleep architecture and long-term health is profoundly detrimental. This narrative review explores the complex relationship between alcohol consumption and sleep disturbances, with a particular focus on the biological mechanisms, epidemiological trends, and clinical implications for recovery.Methods: A comprehensive literature search was conducted across PubMed, ScienceDirect, and Google Scholar databases, covering research from 2001 to 2026. The review synthesized 30 key sources, including meta-analyses, clinical trials, and epidemiological reports from international (WHO, Eurostat) and national (PAN, PARPA) organizations. Inclusion criteria focused on studies detailing alcohol’s impact on sleep architecture, circadian rhythms, and pharmacological interventions in Alcohol Use Disorder (AUD).Results: The evidence confirms that alcohol follows a biphasic effect: initial GABAergic sedation and shortened sleep latency are followed by a "glutamatergic rebound" in the second half of the night. This results in significant REM sleep suppression, increased autonomic stress, and fragmented sleep architecture. Chronobiological data indicate that ethanol disrupts molecular clock gene expression and melatonin secretion, leading to systemic inflammation and cognitive deficits. Furthermore, epidemiological data from Poland and the UK Biobank suggest a causal link between even moderate consumption and chronic insomnia.Conclusions: The "nightcap" myth is biologically refuted; alcohol is a potent chronodisruptor that degrades sleep quality and hinders neurological recovery. In clinical practice, especially within AUD treatment, addressing sleep health through CBT-I and non-addictive pharmacotherapy is a mandatory pillar of relapse prevention. Public health strategies must shift toward a "no safe level" approach to protect the population's circadian and sleep health.